When Facebook is the internet: The role of social media in ethnic conflict - Tuuli Tähtinen (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2024)
This paper investigates whether social media access is associated with increased probability or intensity of ethnic conflict in Myanmar. In this context most people use mobile phones, and particularly the Facebook app, to access the internet. To distinguish the effects of social media from those of the broader internet, I exploit geographic variation in mobile phone coverage as a proxy for Facebook availability. Despite evidence of a hate-campaign utilizing Facebook to reach wide audiences, I do not find that social media access is associated with increased probability or intensity of conflict. The only exception to the null result is variation related to the Rohingya crisis: in this regional setting suggestive evidence points to Facebook availability being associated with slightly higher probability of conflict.
Keywords: D74; O33; 330; internet; social media; conflict; propaganda; Myanmar; Rohingya